2024
DOI: 10.1001/jamanetworkopen.2023.52996
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of 2-Dose HPV Vaccine Series for Postpartum Women

Chailee F. Moss,
Runzhi Wang,
Saumya Sao
et al.

Abstract: ImportancePostpartum human papillomavirus (HPV) vaccination is a promising strategy to increase HPV vaccination uptake in the US, particularly for reaching vaccine-naive women and those who lack health insurance beyond the pregnancy period. However, completion of the 3-dose vaccine regimen is challenging.ObjectiveTo evaluate the immunogenicity of a 2-dose postpartum HPV vaccination regimen (0 and 6 months) and assess whether it is noninferior to a 3-dose postpartum HPV vaccination regimen (0, 1-2, and 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Further, data in 2024 have demonstrated that the 2-dose vaccine schedule was noninferior to the 3-dose vaccine in postpartum patients aged 15 to 46 years, although this recommendation is not officially endorsed. 23 At this time, the WHO recommends a 3-dose vaccination schedule in persons 15 years or older, or those younger than 15 years known to be immunocompromised by disease such as HIV. 24 Currently, there is no established evidence to support a booster vaccination.…”
Section: Primary Prevention: Vaccinationmentioning
confidence: 99%
“…Further, data in 2024 have demonstrated that the 2-dose vaccine schedule was noninferior to the 3-dose vaccine in postpartum patients aged 15 to 46 years, although this recommendation is not officially endorsed. 23 At this time, the WHO recommends a 3-dose vaccination schedule in persons 15 years or older, or those younger than 15 years known to be immunocompromised by disease such as HIV. 24 Currently, there is no established evidence to support a booster vaccination.…”
Section: Primary Prevention: Vaccinationmentioning
confidence: 99%
“…Further, data in 2024 have demonstrated that the 2-dose vaccine schedule was noninferior to the 3-dose vaccine in postpartum patients aged 15 to 46 years, although this recommendation is not officially endorsed. 23 At this time, the WHO recommends a 3-dose vaccination schedule in persons 15 years or older, or those younger than 15 years known to be immunocompromised by disease such as HIV. 24 Currently, there is no established evidence to support a booster vaccination.…”
Section: Primary Prevention: Vaccinationmentioning
confidence: 99%